Mengupayakan Manajemen Media Massa yang Menghargai Jurnalis - Bambang MBK (Jurnal Komunikasi, 2009)
There are many mass media organizations in Indonesia that pay their journalists' salary in a very low amount This condition creates a lot of negative impacts, especially to media role as the fourth estate in a democratic society. This article suggests a new perspective for media management to put consideration on this matter. Thus, universities which have communication department have an important role to integrate this issue into their curriculum. Media management lectures, then, is not only consist of theoretical and practical matters in operating a media. But, these also consist of awareness of the joumalist rights.